The Association Between Perceived Health Status and Health Information Communication Channels. Issue 11 (1st November 2016) - Bounsanga, Jerry; Voss, Maren Wright; Crum, Anthony Bryan; Hung, Man
Abstract : Varying types of health information sources may influence health outcomes, but not much is known about their impact. The purpose of our study was to explore the association between health information sources and individuals' health status. A total of 14, 966 participants who responded to the Annenberg National Health Communication Survey between 2005 and 2012 were included. Controlling for demographics, comorbidities, communication patterns, and socioeconomic status, we utilized regression analysis to examine the relationship between sources of health information and perceived health status. Included in the study were a total of 8, 103 females and 6, 863 males between 18 and 101 years old ( M = 49.14, SD = 16.13). Health information from the Internet and pharmaceutical companies was significantly associated with better health status ( p < .05), whereas information from social media, health care apps, news outlets, and health care companies was not. Information from the Internet was significantly associated with better health status, suggesting that health information from the Internet may have benefits. However, use of social media and health care apps did not relate to better health status, which may indicate that these sources are not as useful to consumers or that these sources have not yet saturated the health information marketplace.